Sarcoidosis: A great mimicker of lymphoma: A case report - Subramanian, Vathul B; Basavanagowdappa, Hathur; Kulkarni, Tanmay (Indian Journal of Case Reports, 2025)
Sarcoidosis is a chronic inflammatory condition of multifactorial origin. Positron emission tomography-computed tomography (PET-CT) is a useful tool for diagnosing and prognosticating the disease. Here, we present the case of a 62-year-old female, a known diabetic, who presented with a history of progressive weight loss despite optimal control of her diabetes. X-ray and ultrasound abdomen showed features of generalized lymphadenopathy, and PET-CT findings were suggestive of lymphoma. A biopsy of the lymph node revealed non-caseating granuloma, and serum angiotensin-converting enzyme levels were not elevated. Diagnosis of sarcoidosis was considered, and started on oral steroids. An interval CT scan showed a reduction in the size of the lymph nodes and an improvement in symptoms. Hence, physicians should use clinical, radiological, and pathological tools together to differentiate sarcoidosis from other inflammatory disorders with generalized lymphadenopathy.